Mechanisms and kinetics of the crystal thickening of poly(butadiene)-block-poly(ethylene oxide) during annealing within the melting range. (July 2015) - Hölzer, Stefan; Büttner, Tobias N.; Schulze, Robert; Arras, Matthias M.L.; Schacher, Felix H.; Jandt, Klaus D.; Schubert, Ulrich S.
Graphical abstract: Highlights: The long-period of PB- b -PEO can be tailored by controlled annealing. We studied the underlying mechanisms and kinetics by t - T -SAXS and DSC. Three different annealing regimes were identified. Abstract: Self-assembled nanostructures of crystallizable block copolymers can be tuned by controlled crystal thickening during annealing. In this contribution, we present a strategy, based on time- and temperature-dependent DSC, SAXS and WAXS measurements, which enables to study, both, the mechanisms and kinetics of crystal thickening and the respective morphological development, exemplarily discussed for the soft-confined PB- b -PEO block copolymer. Thereby, DSC based PEO crystal thickness distributions yield qualitative information about the mechanisms during annealing. Conclusions on the kinetics and the absolute long-period growth due to crystal thickening can be drawn from the time- and temperature-dependent SAXS investigations, by calculating the average long-period and its deviations from the SAXS reflection position and shape, respectively. By this combined study, three annealing regimes were observed. (i) At low annealing temperatures Ta, steady lamellae-thickening was found, due to defect healing of the PEO crystals. (ii) Thermal fractionation was observed at intermediate Ta, due to the exclusion of shorter PEO chains from the crystals. (iii) Annealing close to and above the peak melting temperature, self-nucleation of the molten PEO fractions dominated. The combination of the applied techniques provides deeper insights into the kinetics and ordering mechanisms of the controlled long-period growth by crystal thickening under variable confinements, which enables to tailor the morphology of the block copolymer within several nanometers, without changing the degree of polymerization.